2022
DOI: 10.3390/cancers14122992
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Whole-Body Baseline CT Radiomics and Clinical Parameters to Predict Response and Survival in a Stage-IV Melanoma Cohort Undergoing Immunotherapy

Abstract: Background: This study investigated whether a machine-learning-based combination of radiomics and clinical parameters was superior to the use of clinical parameters alone in predicting therapy response after three months, and overall survival after six and twelve months, in stage-IV malignant melanoma patients undergoing immunotherapy with PD-1 checkpoint inhibitors and CTLA-4 checkpoint inhibitors. Methods: A random forest model using clinical parameters (demographic variables and tumor markers = baseline mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Three previous smaller studies have investigated radiomics for this purpose, with conflicting findings. The studies by Trebeschi et al [22] and Peisen et al [23] report a significant discriminative value of radiomics for treatment outcomes (AUROC=0.78 on a dataset of 80 patients, and AUROC=0.64 on a dataset of 262 patients, respectively). In contrast, Brendlin et al [24] reported a non-discriminative performance, despite using a very similar methodology (AUROC=0.50 in 140 patients).…”
Section: Radiomics Are By Now An Established Modality For Diagnosis P...mentioning
confidence: 99%
“…Three previous smaller studies have investigated radiomics for this purpose, with conflicting findings. The studies by Trebeschi et al [22] and Peisen et al [23] report a significant discriminative value of radiomics for treatment outcomes (AUROC=0.78 on a dataset of 80 patients, and AUROC=0.64 on a dataset of 262 patients, respectively). In contrast, Brendlin et al [24] reported a non-discriminative performance, despite using a very similar methodology (AUROC=0.50 in 140 patients).…”
Section: Radiomics Are By Now An Established Modality For Diagnosis P...mentioning
confidence: 99%
“…A recent study in patients with advanced NSCLC who were treated with ICI presented an approach that evaluates dynamic changes in specific tumor radiophenotypic attributes between baseline and post-treatment CT scans [40]. In addition, a few studies have extracted imaging biomarkers to assess the correlation between pretreatment CT texture parameters and survival prediction in patients with metastatic melanoma who received anti-PD-1 monoclonal antibodies [41][42][43][44]. Study findings by Trebeschi et al on a small melanoma cohort proved an association between tumor textural radiomic patterns and responses to immunotherapy [45].…”
Section: Discussionmentioning
confidence: 99%
“…Radiomic features are highly dependent on image acquisition (machine variability) and reconstruction (software variability) [20]. Current studies show that while there are statistically significant radiomic features associated with overall survival and progression free survival, these features are based on small sample sizes and it would be difficult to have them universally accepted [23,24,55].…”
Section: Methodsmentioning
confidence: 99%
“…These methods could assist with a more precise melanoma diagnosis and individualised therapy. They can be used to predict immunotherapy response in metastatic melanoma prior to commencing treatment [20,22,[24][25][26]. Furthermore, radiomics can aide in-vivo classification of disease, reducing invasive diagnostic testing such as biopsy [21].…”
Section: Current Utilitymentioning
confidence: 99%
See 1 more Smart Citation